A) x=-5
Step-by-step explanation
![-8x+5x-9=6](https://img.qammunity.org/2023/formulas/mathematics/college/g9nmsnu11zllaqhal6r9dfjptxawytggd9.png)
Step 1
add like terms
![\begin{gathered} -8x+5x-9=6 \\ -3x-9=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lh8hbmoitkfl8lejgbw6x86wrcqpgm7do9.png)
Step 2
now, add 9 in both sides. (If two expressions are equal to each other, and you add the same value to both sides of the equation, the equation will remain equal.)
![\begin{gathered} -3x-9=6 \\ \text{add 9 in both sides} \\ -3x-9+9=6+9 \\ -3x=15 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zgw64xe2pdzswx9hzz5mmmdy663zj11c6e.png)
Step 3
finally, divide both sides by -3
![\begin{gathered} -3x=15 \\ \text{divide by -3} \\ (-3x)/(-3)=(15)/(-3) \\ x=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5g2y2umhzqrpe8j8s9qjw0embip3muwgcl.png)
so, the answer is A) x=-5
I hope this helps you